Voices from the Classroom: English teachers’ narratives about the pandemic, ICTs and the construction of professional identity - Uchôa, Jose Mauro Souza; Andrade , Gleiciane Lima; Sousa, Rodrigo Martins de (The ESPecialist, 2025)
This article aims to reflect on the identity under construction of the English as a Foreign Language (EFL) teacher in the context of the Covid-19 pandemic, demonstrating how social isolation has changed daily life and teaching practices in relation to the use of digital information technologies and communication (DICTs). The theoretical basis of this article focuses on the decontextualization of identity in modernity and the view of discourse and social identity based on local language practices. Regarding the methodological approach, the study is anchored in the qualitative research paradigm, with Narrative Inquiry procedures in which participants write narratives and construct meanings about the teaching process. The participants are two basic education teachers in the process of continuing education, an EFL teacher from a public school and an EFL teacher from a public language course, both working in the teaching context of the state of Acre, in Brazil. Two narratives were confirmed based on the theoretical framework that made it possible to create meaning about this experience. The data revisited during the investigation reveals the fluidity of teaching identities during the pandemic period and the EFL teacher’s identity practices in the face of the pandemic, with the intensification of the use of TDICs.